Faktor Yang Berhubungan Dengan Kelelahan Mata Pada Pegawai Di UPT War Room Diskominfo Makassar - Syakirah Inayah; Nurgahayu; Nurul Hikmah B (Window of Public Health Journal, 2026)
Eye fatigue, also known as asthenopia, is a condition caused by excessive use of the visual system, resulting in impaired visual function. A group of eye and vision-related symptoms associated with prolonged use of computers and other electronic devices is known as Computer Vision Syndrome (CVS). Preliminary observations among employees at the UPT War Room of the Makassar Communication and Information Office revealed several complaints related to eye fatigue, including burning eyes (36%), red eyes (54%), eye pain (63%), dry eyes (45%), and headaches (45%). This study aimed to determine the factors associated with eye fatigue among employees at the UPT War Room Diskominfo Makassar, providing insights relevant to health professionals and researchers interested in occupational eye health. This study employed a quantitative approach with a cross-sectional design. The study population consisted of all employees at the UPT War Room Diskominfo Makassar, totaling 52 respondents. Data were analyzed using univariate and bivariate analyses. The results showed significant associations between work duration and eye fatigue (p=0.033), age and eye fatigue (p=0.030), viewing distance and eye fatigue (p=0.034), refractive disorders and eye fatigue (p=0.042), as well as body posture and eye fatigue (p=0.038), indicating these factors are statistically linked to eye fatigue risk. Based on the findings, it can be concluded that work duration, age, viewing distance, refractive disorders, and body posture are associated with eye fatigue among employees at the UPT War Room Diskominfo Makassar. These insights can guide targeted interventions to reduce eye fatigue and improve occupational health outcomes.